2009
DOI: 10.3892/ijo_00000449
|View full text |Cite
|
Sign up to set email alerts
|

Risk of gastric cancer is associated with the MUC1 568 A/G polymorphism

Abstract: Abstract. Identifying the genetic variants that alter MUC1 protein expression may further our understanding of the risk for development of gastric cancer (GC). We used PCR-SSPs to identify the genotype of MUC1 A/G polymorphism at its 568 site of exon 2 and immunohistochemistry to detect MUC1 protein expression in GC patients and non-cancer subjects and analyzed the association between this polymorphism and MUC1 protein expression. We found that the frequency of AA genotype was significantly high in the GC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It is known that HPV18 oncoproteins can exert their oncogenic properties through targeting AKT [29], extracellular signal-regulated kinase (ERK) [30] and metalloprotease (MMP) [31, 32] pathways in cervical cancer cells, leading to cell survival, proliferation and metastasis. To date, the involvement of HPV18 oncoproteins in perturbing these pathways in esophageal and tongue SCC cell lines has not been clearly defined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that HPV18 oncoproteins can exert their oncogenic properties through targeting AKT [29], extracellular signal-regulated kinase (ERK) [30] and metalloprotease (MMP) [31, 32] pathways in cervical cancer cells, leading to cell survival, proliferation and metastasis. To date, the involvement of HPV18 oncoproteins in perturbing these pathways in esophageal and tongue SCC cell lines has not been clearly defined.…”
Section: Resultsmentioning
confidence: 99%
“…HPV-positive cells require HPV oncoproteins to survive and proliferate, which can occur through perturbation of signaling pathways, including AKT [29], ERK [30], suppression of the caspase cascade [42, 43], and MMPs for migration [31, 32]. AKT is known to possess a pro-survival role [41, 47], while ERK1/2 appears to be a dual-faced protein: anti- or pro-apoptotic kinase [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent meta-analysis studies have shown that the G allele of MUC1 rs4072037 is associated with a decreased risk of GC [38,39]. MUC1 rs4072037 affects the gene promoter, leading to reduced transcriptional activity and MUC1 [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood samples obtained from the study participants using the phenol-cholesterol method according to a standard procedure (45). The Matrix-Assisted Laser Desorption Ionization Time of Flight (MALDI-TOF) genotyping system was used to genotype 612 individuals for 28 inflammation-related gene polymorphisms.…”
Section: Snp Genotypingmentioning
confidence: 99%